Participatory governance for sustainable management of natural resources in the Great Limpopo Transfrontier Park: The case of Parque Nacional do Limpopo, Moçambique - Nhancale, Camilo Correia (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Conservation Ecology and Entomology)--University of Stellenbosch, 2007.